Mapping neurotransmitter systems to the structural and functional organization of the human neocortex - Hansen Justine Y.; Shafiei Golia; Markello Ross D.; Smart Kelly; Cox Sylvia M. L.; Nørgaard Martin; Beliveau Vincent; Wu Yanjun; Gallezot Jean-Dominique; Aumont Étienne; Servaes Stijn; Scala Stephanie G.; et al. (NATURE PORTFOLIO, 2022)
Neurotransmitter receptors support the propagation of signals in the human brain. How receptor systems are situated within macro-scale neuroanatomy and how they shape emergent function remain poorly understood, and there exists no comprehensive atlas of receptors. Here we collate positron emission tomography data from more than 1,200 healthy individuals to construct a whole-brain three-dimensional normative atlas of 19 receptors and transporters across nine different neurotransmitter systems. We found that receptor profiles align with structural connectivity and mediate function, including neurophysiological oscillatory dynamics and resting-state hemodynamic functional connectivity. Using the Neurosynth cognitive atlas, we uncovered a topographic gradient of overlapping receptor distributions that separates extrinsic and intrinsic psychological processes. Finally, we found both expected and novel associations between receptor distributions and cortical abnormality patterns across 13 disorders. We replicated all findings in an independently collected autoradiography dataset. This work demonstrates how chemoarchitecture shapes brain structure and function, providing a new direction for studying multi-scale brain organization.